Effects conjugated linoleic acid, high-oleic sunflower oil and fish dietary supplementation on laying hen egg quality - Cachaldora, P.=700 1 Garcia-Rebollar, P.; Alvarez, C.; Mendez, J.; De Blaá, J.C.
(Es, En)
ilus., 34 ref.
Keywords: GALLINA PONEDORA; DIETA; ACIDOS GRASOS; ACIDO LINOLEICO; ACEITE DE PESCADO; ACEITE DE GIRASOL; PRODUCTIVIDAD; ESPAÑA